PENERAPAN AKUNTANSI KEUANGAN BERBASIS TEKNOLOGI DENGAN MENGGUNAKAN APLIKASI MIND YOUR OWN BUSINESS (MYOB) PADA USAHA MIKRO YUDI MOTOR SURABAYA - Avita Sekar Safitri; Chasan Azari; Yanda Bara Kusuma (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2020)
This is a financial accounting study using the application of MYOB accounting in Yudi Motor micro business. The study aims to produce quality financial report according to the accounting principles. It uses descriptive qualitative method regarding the application of MYOB accounting through condensation data, presentation, conclusion, and verification. There are two informants in the analysis from the company owner and the financial staff. The results indicate that the informants have some difficulties in understanding accounting and applying MYOB accounting. Furthermore, the accounting cycle starts from general journal, ledger, and it produces financial report consisting of trial balance report, balance report, income statements and cash flow report. The finding concludes that two informants haven’t understood MYOB accounting manually and automatically. For this reason, the researcher educates them in compiling theoretical and practical accounting manually and automatically. As the result, two informants are able to understand the application well after the second assistance. Moreover, the study suggests the use of MYOB accounting application to process the financial data effectively and efficiently, and to produce quality financial report according to the accounting principles.